Assessing the Industrial Effluent Effect on Irrigation Water Quality and Farm Soil near Kombolcha Town, Ethiopia - Mohammed Jemal Awol; Amare Tiruneh Adugna; Kamaraj M (Journal of Chemistry)
This study evaluated various industrial effluents’ effect on irrigation water quality and farm soil near Kombolcha town. Several industries such as brewery, steel iron, textile, and tannery have been installed near the Borkena River that crosses Kombolcha town. Representative samples of irrigation water and farm soil were collected from the upper and down part of Borkena river. The upper site was used as a control as it was not contaminated by industrial effluents. The analysis for selected parameters showed that the downstream irrigation water quality had mean concentrations of pH = 8.54, magnesium (Mg+2) = 5.27 mg/l, carbonate (CO3−2) = 1.25 mg/l, bicarbonate (HCO3−) = 9.10 mg/l, copper (Cu) = 0.21 mg/l, chromium (Cr) = 0.31 mg/l, and cadmium (Cd) = 0.03 mg/l which were above the permissible limit of the Food and Agriculture Organization’s (FAO’s) irrigation water quality standard. The mean concentrations of electric conductivity (EC) = 0.96 ds/m, sodium (Na+) = 3.35 mg/l, chloride (Cl−) = 7.67 mg/l, and total dissolved solids (TDS) = 612.98 mg/l were slightly and moderately restricted for irrigation. Moreover, the concentration of heavy metals, calcium (Ca+2) = 16.61 mg/l, iron (Fe) = 4.25 mg/l, manganese (Mn) = 0.18 mg/l, and lead (Pb) = 0.47 mg/l, was below the permissible limit of the FAO and nonrestricted. However, the mean concentration of EC, HCO3−, Cu, Cr, Cd, and TDS for downstream-irrigated farm soil samples was above the permissible limit of the FAO. The concentration of most selected parameters in downstream farm soil was also decreasing along with depth except pH, CO3−2, and HCO3-. Generally, there is a significant quality difference (at P ≤ 0.05) between the upstream and downstream irrigation water quality on the parameters of Mg+2, Cl−, Pb, and Cu.